CBCT Post-Processing Tools to Manage the Progression of Invasive Cervical Resorption: A Case Report - Vasconcelos,Karla de Faria (2016)
Abstract This case report aimed to highlight the usefulness of cone beam computed tomography (CBCT) and its post-processing tools for the diagnosis, follow-up and treatment planning of invasive cervical resorption (ICR). A 16-year-old female patient was referred for periapical radiographic examination, which revealed an irregular but well demarcated radiolucency in the mandibular right central incisor. In addition, CBCT scanning was performed to distinguish between ICR and internal root resorption. After the diagnosis of ICR, the patient was advised to return shortly but did so only six years later. At that time, another CBCT scan was performed and CBCT registration and subtraction were done to document lesion progress. These imaging tools were able to show lesion progress and extent clearly and were fundamental for differential diagnosis and treatment decision.